A simplified acute physiology score in the prediction of acute aluminum phosphide poisoning outcome - Soltaninejad, Kambiz; Shadnia, Shahin; Mehrpour, Omid (Indian journal of medical sciences, 2010)
Background : Aluminum phosphide (AlP) is used as a fumigant. It produces phosphine gas, which is a mitochondrial poison. Unfortunately, there is no known antidote for AlP intoxication, and also, there are few data about its prognostic factors. AIMS: The aim of this study was to determine the impact of the Simplified Acute Physiology Score II (SAPS II ) in the prediction of outcome in patients with acute AlP poisoning requiring admission to the Intensive Care Unit (ICU). Materials and Methods : This was a prospective study in patients with acute AlP poisoning, admitted to the ICU over a period of 12 months. The demographic data were collected and SAPSII was recorded. The patients were divided into survival and non-survival groups due to outcome. Statistical Analysis : The data were expressed as mean +- SD for continuous or discrete variables and as frequency and percentage for categorical variables. The results were compared between the two groups using SPSS software. Results : During the study period, 39 subjects were admitted to the ICU with acute AlP poisoning. All 39 patients required endotracheal intubation and mechanical ventilation in addition to gastric decontamination with sodium bicarbonate, permanganate potassium, and activated charcoal, therapy with MgSO 4 and calcium gluconate and adequate hydration. Among these patients, 26 (66.7%) died. SAPSII was significantly higher in the non-survival group than in the survival group (11.88 +- 4.22 vs. 4.31 +- 2.06, respectively) (P < 0.001). Conclusion : SAPSII calculated within the first 24 hours was recognized as a good prognostic indicator among patients with acute AlP poisoning requiring ICU admission.